Creation of a 3D animated film titled "Made and the Lost Spirit" - Krishna, Ida Bagus Ista; Dinata, Ramanda Dimas Surya; Jaya, Kadek Prana; Rimbawan, Ari (International Journal of Engineering, Science and Information Technology, 2025)
3D Animation is a form of Animation that uses three-dimensional objects so that the visuals presented look more real and immersive. 3D objects can be rotated and viewed from various perspectives. Bali, with its unique cultural values, should not only be a tourist attraction but can also be the basis for creating multiple creations, especially in animation design, which can be an attraction and introduce Balinese culture to the international arena. In this research, the Animation tells the story of a child named Made who did not have a parental figure from childhood and lived alone with his grandfather in the village. The village where Made lives is not safe; evil demons have destroyed it. This made Made trained by his grandfather to become a strong child worthy of adventure to save the village and find his missing parents. Made's adventure is not alone; Made is accompanied by a good spirit in the form of a barong named Dharma, who will guide Made's journey. Made's efforts are constantly hampered by his older brother, who is an evil spirit with great power, and the only way Made can stop his grandfather is by joining forces with Dharma. The method used in this research is computer graphics with pre-production, production, and post-production stages. This research aims to design an animation entitled Made and The Lost Spirit inspired by the values of the Galungan holiday celebration in Bali. Apart from this, the novelty of this Animation lies in highlighting Balinese culture and ornaments in the visual elements presented in the creation of international standard quality animation with intellectual Property owned by the author.